Determinants of Factors Influencing Low Birth Weight (BBLR) on The Growth of Babies Aged 1-6 Months - Aisya Ratna Billa Dhayundra Putri Rajjat; Noor Azizah; Ummi Kulsum (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to determine the relationship between the determinants of BBLR factors and the growth of babies aged 1–6 months in the working area of the Kaliwungu Health Center, Kudus Regency. Research Method: The study used an observational analytical design with a rhetorative approach with a total sampling technique in infants aged 1–6 months who had a history of BBLR. Data were collected through medical records and observation sheets, including maternal characteristics (age, education, occupation, parity, preterm gestational age), pregnancy complications (KEK, anemia, preeclampsia, anxiety), and baby growth based on body weight, then analyzed univariate and bivariate using Fisher's Exact Test. Results and Discussion: The results showed no statistically significant relationship between maternal characteristics and pregnancy complications or baby growth (p > 0.05). Most BBLR babies show normal growth according to age-based weight indicators, although there are variations, such as catch-up growth, and the need for follow-up monitoring. Implications: It was concluded that maternal factors do not significantly affect the growth of BBLR babies, so it is still necessary to prevent and optimally monitor pregnancy and baby growth.